1984
DOI: 10.1084/jem.159.4.1201
|View full text |Cite
|
Sign up to set email alerts
|

Common protective antigens of group A streptococcal M proteins masked by fibrinogen.

Abstract: The surface M protein of group A streptococci is the principal virulence factor of these organisms. Streptococci lacking M protein are efficiently opsonized by the alternate complement pathway (1, 2) and in consequence are rapidly ingested and killed by host leukocytes. Streptococci possessing surface M protein are neither opsonized nor ingested unless antibody to the M protein is present (3). Two hypotheses, which are not mutually exclusive, have been advanced to explain the antiphagocytic properties of M pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…The antiphagocytic behavior of group A streptococci is also mediated by the binding of fibrinogen to the surface of M protein (555)(556)(557). Fibrinogen binding to the surface of group A streptococci blocks the activation of complement via the alternate pathway and greatly reduces the amount of C3b bound to streptococci, which therefore reduces phagocytosis by polymorphonuclear leukocytes (247).…”
Section: Host Response To Infection: Opsonization and Phagocytosismentioning
confidence: 99%
“…The antiphagocytic behavior of group A streptococci is also mediated by the binding of fibrinogen to the surface of M protein (555)(556)(557). Fibrinogen binding to the surface of group A streptococci blocks the activation of complement via the alternate pathway and greatly reduces the amount of C3b bound to streptococci, which therefore reduces phagocytosis by polymorphonuclear leukocytes (247).…”
Section: Host Response To Infection: Opsonization and Phagocytosismentioning
confidence: 99%
“…Virulent GAS multiply in nonimmune human blood because the M protein specifically binds numerous plasma proteins that block or interfere with the activation and deposition of complement (15). Antibodies against the N-terminal regions of the M protein are opsonic and are able to bind to the M epitopes that extend beyond the layer of human plasma proteins covering the cell surface (18). In the current study, we have shown that serotype M65 GAS expressed three distinct cell wall proteins that contained bactericidal epitopes.…”
Section: Discussionmentioning
confidence: 84%
“…2). In order to mimic the potential in vivo conditions, antibody binding assays were performed in the presence of human plasma, which contains multiple proteins that bind to the bacterial surface (15)(16)(17) that can alter the binding of functional antibodies (18). The M, Mrp, and Spa peptide antisera each reacted with the surface of M65 streptococci in a semicircular pattern at the pole of each coccus, a location that represents the mature cell wall with fully inserted integral proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that the ability of strains of S . pyogenes to bind fibrinogen enables them to escape the host defence mechanisms (Whitnack et al, 1984) and the strain of S . pyogenes used in the current study did bind fibrinogen very effectively (22% of the added protein).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly SMG strains were tested for their ability to adhere to saliva-coated hydroxy-apatite and buccal epithelial cells (Handley etal., 1987), to bind fibrinogen (Whitnack et al, 1984) and fibronectin (Abraham etal., 1983;Babu and Dabbous, 1986;Hogg and Manning, 1989), and to co-aggregate with strains of Veillonella and Actinomyces (Cisar et al, 1979;Weerkamp and McBride, 198 1). Hydrophobicity and surface charge may contribute to adhesion; therefore these properties were also investigated.…”
Section: Introductionmentioning
confidence: 99%